Pengaruh Model Pembelajaran Read Answer Discuss Explain Create Berbantuan Media Puzzle terhadap Kemampuan Bernalar Kritis Pendidikan Pancasila pada Kelas IV Sekolah Dasar - Aini, Annisa Qurrotul; Ismiyanti, Yulina (Innovative: Journal Of Social Science Research, 2025)
This study aims to determine the effect of Read Answer Discuss Explain Create Learning model assisted by puzzle media on the ability to critically reason pancasila education. The research method useed in this study is a quantitative method in pre experimental with the type of research one group pretest-posttest design. The sample used was 11 fourth grade students of SDN Pulo. Data collections techniques in the form of test techniques, using critical reasoning ability test questions. From the results of the paired sample t test hypothesis test, the sig. (2-tailed) 0,000 < 0,05, because the sig value. (2-tailed) < α then H_o is rejected. So there is a significant difference in critical reasoning ability between before and after using the RADEC learning model assisted by puzzle media. So it can be concluded that there is an effect of the application of the Read Answer Discuss Explain Create learning model on the Critical Reasoning Ability of Grade IV Students of SDN Pulo.